Enhancing Employee Productivity: The Mediating Role of Work Discipline in Work Environment and Compensation Strategies - Elis Sujimah; Musoli (Journal of Organizational and Human Resource Development Strategies, 2025)
Achieving organizational goals requires competent human resources, where employee productivity serves as a key performance indicator. High productivity reflects efficient and effective work, influenced by factors such as the work environment, compensation, and work discipline. This study investigates the mediating role of work discipline in the relationship between work environment, compensation, and employee productivity. Using a quantitative approach, the research surveyed all 90 employees of the Public Works, Housing, and Settlement Areas Department in Bantul Regency through a census sampling method. Data collected via questionnaires were analyzed using SPSS 25. Results revealed that both the work environment and compensation significantly enhance work productivity. Furthermore, these factors positively influence work discipline, which itself has a significant impact on productivity. Critically, work discipline mediates the effects of the work environment and compensation on productivity. The study confirms all hypotheses, highlighting the importance of fostering a supportive work environment, fair compensation, and strong work discipline to optimize employee performance. These findings offer practical insights for organizational strategies aimed at boosting productivity through integrated human resource management.